A COMPREHENSIVE REVIEW ON COMORBID DEPRESSION IN PATIENTS WITH EPILEPSY - Mammen, Keziya Ann; S, Sathesh Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Epilepsy is one of the common neurological disorders that are seen worldwide. It can also affect a person's social, mental, and physiological well-being and thus restricts and disables the common living of man. Depression as such has been well reported in patients with epilepsy, and also depression itself remains a factor that can lead to the development of epilepsy. Increased rates of suicidal tendencies are also associated with depression both in men and women. Depression is further extended in affecting the quality of life in epileptic patients. Depressive rates are found to have a higher value in epileptic patients when compared with the normal population. This article aims to produce a comprehensive review of the epidemiological considerations, clinical findings and management strategies for depression associated with epilepsy.